Why I Am a Salafi - Matthew D. Taylor (International Institute of Islamic Thought, 2018)
Anyone who was not familiar with Michael Muhammad Knight’s oeuvre and picked up his Why I Am a Salafi based upon the title, thinking it would be a straightforward explanation and defense of Salafism, would be quickly disabused of that impression. Knight begins this memoir/theological exploration/ postmodern deconstruction with an extended anecdote about his experience of praying at a Los Angeles mosque while coming down from a drug-induced hallucination brought on by his intentional consumption of Amazonian ayahuasca tea, and the book gets stranger from there. This transgressive episode of praying while high becomes a touchstone for Knight in his rethinking of his own Muslimness, the origins of the Islamic tradition, and his life-journey through a variety of controversial and eccentric communities on the fringes of the American Muslim community. In Knight’s previous body of work—from his 2004 novel The Taqwacores (Soft Skull Press) about punk-rocking, countercultural American Muslims to his insider-white-man narrative of an esoteric offshoot movement of the Nation of Islam in Why I Am a Five Percenter (Penguin, 2011)—he has long cast himself as an experimental Muslim writer challenging established traditions and organized religion of all kinds. Like some of his other books, Why I Am a Salafi is difficult to categorize. Framed around Knight’s odyssey within American Islam and the diffuse trends that contributed to the development of his distinct perspective, it is part religious autobiography, part analysis of the nebulous concept of Salafism, and part therapy session. Indeed, drawing upon his well-established tendency toward bucking trends and upsetting orthodoxies, Knight quips that in the progressive Muslim circles he tends to run in, labeling himself a Salafi could itself be a form of rebellion. “Depending on whom you want to irritate, Salafis could look like the new punk rock” (29) ...